Gut Mycobiome Dysbiosis Is Linked to Hypertriglyceridemia among Home Dwelling Elderly Danes - Hajar Fauzan, Ahmad; Castro Mejia, Josue Leonardo; Krych, Lukasz; Khakimov, Bekzod; Kot, Witold; Bechshøft, Søren and Højfeldt; Holm, Lars; Faust, Karoline; Nielsen, Dennis Sandris (Cold Spring Harbor Laboratory, 2020)
Gut microbial dysbiosis have been in the etiology of a number of diseases, yet the presence of fungal communities and their possible association with host health are little understood. This study attempts to identify gut microbial fungal associations with the progression of atherogenic dyslipidemia in a population of older adults by investigating the interplay between dietary intake, gut mycobiome composition, plasma and fecal metabolome and anthropometric/body-composition measurements of 100 Danes aged 65 to 81 (69.57 ± 3.64) years. The gut mycobiome composition were determined by high-throughput sequencing of internal transcribed spacer (ITS2) gene amplicons, while the plasma and fecal metabolome was determined by GC-TOF-MS. The gut microbiome of the subjects investigated is home to three main eukaryotic phyla, namely Ascomycota, Basidiomycota and Zygomycota, with genera Penicillium, Candida, and Aspergillus being particularly common. Hypertriglyceridemia was associated with fewer observed fungal species, and Bray-Curtis dissimilarity matrix-based analysis showed significant (P<0.05) clustering according to fasting levels of circulating plasma triglycerides (Tg) and very low-density lipoprotein (VLDL) cholesterol fasting levels, respectively. Interestingly, neither hypertriglyceridemia nor elevated VLDL levels were reflected in the prokaryotic component of the gut microbiome as determined by 16S rRNA gene amplicon sequencing. Higher levels of Tg and VLDL cholesterol significantly associates with increased relative abundance of genus Penicillium, possibly mediated by a higher dietary fat intake (ANOVA, P<0.05), and Aspergillus and Guehomyces were positively associated with SCFAs groups. Collectively, these findings suggest that in older adults’ gut mycobiome dysbiosis is associated with hypertriglyceridemia, a known risk factor for development of cardiovascular disease.